Recycling of Epoxy Moulding Compounds to Develop an Alternative Ceiling Board - Zulhazmi, Nur Ainna; Harun, Hasnida (Progress in Engineering Application and Technology, 2023)
Recycling is the process of repurposing waste into new products and materials where the semiconductor industry uses epoxy molding compounds extensively as a primary material for electronic packaging, the possible financial benefits of using recycled plastic especially polyethylene and agriculture waste of coir fiber and the majority of the residue is frequently burned or thrown at landfills, which could result in resource waste and environmental harm. This study is to determine the potential of EMC, coir fiber and PE as an alternative ceiling board and analyze the quality of the alternative ceiling board by using water absorption, sound absorption and tensile strength test as this focuses on recycling waste material. The alternative ceiling board is produced by using the sandwich method as all three layers are hot pressed together. The data were analyzed after the sample quality analysis was performed. By adding more EMC, it will improve the performance of the alternative ceiling board.